Pengaruh Motivasi, Disiplin, dan Kompensasi Terhadap Kinerja Pegawai Puskesmas Dum Distrik Sorong Kepulauan Kota Sorong - Rosbandi, Rosbandi; Herningsih, Herningsih; Sultan, Zulkifli (Green Publisher Indonesia, 2024)
The purpose of this study was to determine and analyze the effect of motivation, discipline and compensation on employee performance at Dum Public Health Center, Sorong Islands District, Sorong City. The type of research conducted is quantitative descriptive analysis. Sampling of data by distributing questionnaires to 70 employees at Dum Health Center. The results showed that motivation (X1) had a positive effect on the performance (Y) of Dum Health Center employees. Discipline (X2) has a positive and significant effect on the performance (Y) of Dum Health Center employees. Compensation (X3) has a positive and significant effect on the performance (Y) of Dum Health Center employees. Simultaneously Motivation (X1), Discipline (X2), and Compensation (X3) have a positive and significant effect on the Performance (Y) of Dum Health Center employees.